2021
DOI: 10.3390/ijms22126175
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Yamazaki et al. Editing DNA Methylation in Mammalian Embryos. Int. J. Mol. Sci. 2020, 21, 637

Abstract: The authors wish to make the following corrections to our previously published paper [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…3) Kamiya et al suggested a transparent amorphous OS 4) and claimed that an amorphous structure is ideal, 5,6) which is different from the idea of our crystalline IGZO. We discovered c-axis-aligned crystalline IGZO (CAAC-IGZO) [7][8][9] and nanocrystalline IGZO (nc-IGZO) [10][11][12][13] as an intermediate state between single crystal IGZO 1,14,15) and amorphous IGZO. Both CAAC-IGZO and nc-IGZO include fine crystalline clusters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3) Kamiya et al suggested a transparent amorphous OS 4) and claimed that an amorphous structure is ideal, 5,6) which is different from the idea of our crystalline IGZO. We discovered c-axis-aligned crystalline IGZO (CAAC-IGZO) [7][8][9] and nanocrystalline IGZO (nc-IGZO) [10][11][12][13] as an intermediate state between single crystal IGZO 1,14,15) and amorphous IGZO. Both CAAC-IGZO and nc-IGZO include fine crystalline clusters.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve a CAAC structure, a substrate must be heated at a certain temperature during the IGZO deposition. 8,17) Therefore, nc-IGZO, which can be deposited at RT, is considered advantageous in terms of productivity. Although the crystallinity of CAAC-IGZO has generally been verified as in some papers from other research groups, 19) the crystallinity of nc-IGZO has not been studied closely.…”
Section: Introductionmentioning
confidence: 99%